Differences in web features between two sympatric Leucauge species (Araneae: Tetragnathidae) suggest a trade-off in prey capture strategy - Vargas Gamboa, Alejandra (2021)
The design of orb webs is affected by multiple abiotic (e.g., wind, available space), biotic (e.g., prey availability, predation), and species specific (e.g., spider size) factors. Thus, some features of each spider web are expected to reflect the combined effect of such factors. We compared the relationship of spider size and web inclination on the area of different sections of the orb web and other features (e.g., number or radii) between two sympatric Leucauge species (Leucauge sp., and L. argyra (Walckenaer, 1841), Tetragnathidae). Leucauge sp. was smaller and constructed smaller webs across a wider range of inclinations than L. argyra. Other features of the web, e.g., capture area, and hub area, but not the number of adhesive spiral turns and number of radii, were also larger in webs of L. argyra. The inclination was greater in webs of Leucauge sp., but the asymmetry of webs did not differ between species, though, it correlated negatively with the total area of the web of both species, as in other orb-weavers. The characteristics of each species’ web suggest that L. argyra optimizes prey interception, while Leucauge sp. optimizes stopping and retention of large prey.